Parotid Dermoid Cyst: A Case Report. (April 2013) - Birsan, Christina; Raza, Anwar; Cobb, Camilla
A dermoid cyst arising in the parotid is rare and usually represents the rare first branchial cleft type II anomaly, which can have morphology similar to a dermoid cyst. This study reports the case of a 20-year-old woman who presented with a parotid mass, which on histologic review was consistent with a dermoid cyst. This appears to be the first case report of a parotid dermoid cyst with focus on the gross and histopathologic findings and to be presented in a histopathology focused journal. The discussion includes the clinical presentation, imaging findings, gross pathology, histologic features, and differential diagnosis of parotid dermoid cysts. Although there was no prior fine needle aspiration (FNA) of the lesion in this case, parotid masses are commonly subject to FNA prior to excision. Therefore, a brief review of the FNA findings in dermoid cysts is also included.